Randomized Trial Based on the Common-Sense Model of Self-regulation to Increase Child Dental Visits. (October 2019) - Nelson, S.; Milgrom, P.; Albert, J.M.; Selvaraj, D.; Cunha-Cruz, J.; Curtan, S.; Copeland, T.; Heima, M.; Rothen, M.; Beck, G.; Ferretti, G.; Riedy, C.
Introduction: School screening and the note home (pinned to a backpack) informing parents/caregivers that their child needs to see a dentist have not been effective. Objectives: The Family Access to a Dentist Study (FADS) evaluated the effectiveness of school interventions based on the common-sense model of self-regulation (CSM) among K–4 children needing restorative treatment. Methods: FADS was a multisite double-blind randomized controlled trial with 5 arms. FADS tested a CSM-driven referral letter and dental information guide (DIG) to move caregivers from inaccurate to accurate perceptions of dental caries. Six school districts from Ohio and Washington (14 schools) participated in school years 2015 to 2016 and 2016 to 2017. A total of 611 caregivers were randomized, and 86% ( n = 597 children) completed the exit examination. The primary outcome was receipt of care based on a change in oral health status determined clinically within 1 school year. Results: In accordance with our primary aims, 5 arms were collapsed into 3: CSM letter and reduced CSM letter (combined), CSM letter + DIG and reduced CSM letter + reduced DIG (combined), and standard letter. Among all sites, 39.7% received restorative care (237 of 597). Combined analysis of sites revealed that the CSM referral letter (with and without the DIG) did not increase dental visits when compared with the standard letter. However, for combined sites (East Cleveland, Ohio; Washington), the CSM + DIG increased dental visits when compared with standard letter in univariate analysis (51.3% vs. 40.9%), indicating 1.6-times increased odds of a dental visit (95% CI, 0.97 to 2.58) after imputation and adjustment for covariates. The CSM + DIG group had 1.9-times increased odds (95% CI, 1.21 to 3.08) of care when compared the CSM letter alone. Conclusion: A CSM-driven approach to informing caregivers of the chronic nature of caries with resources in an illustrative manner can increase the benefit of school oral health screening (ClinicalTrials.gov NCT02395120). Knowledge Transfer Statement: A school dental referral (note home) that tells a parent that the child has cavities has not been effective. In this trial, a referral based on the common-sense model of self-regulation increased follow-up care for children with restorative needs.